Storage location assignment problem in a warehouse system - Sushant Gupta. (2014)
In a warehouse management system, there are a large number of items that needs to be handled efficiently with an emphasis on timely execution andoptimum utilization of storage space. A mathematical model is presented that involves the use of randomized storage and class based storage policy solving the storae assignment problem by reducing the transit time. The results are analyzed with the use of two and four forklifts in a warehouse. The thesis examines the robustness of the proposed method using several case studies of different number of forklifts.